Video-Based Moral Learning: An Internalization of Values in Early Childhood - Rodhatul Jennah; Mazrur Mazrur; Rita Rahmaniati (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Moral education is a vital part of the educational process. Moral teaching cannot be completely conceptual and theoretical but must also be practical, so additional learning media is needed. This study aims to show the important value of learning media in teaching morals, especially with video media. Using the five stages of ADDIE's research design, namely analysis, design, development, implementation and evaluation, this research also intends to design a video learning moral value based on Banjar culture. The results show that this learning video is indeed very necessary and has proven to be effective in the moral learning process at the early childhood level. Video media can provide clear and practical illustrations of instilled moral values and students feel happy and enthusiastic. It is even more important that this learning video raises the local wisdom of Banjar culture as the basis for the values being taught.